Impact of droughts on water provision in managed alpine grasslands in two climatically different regions of the Alps. Issue 8 (3rd February 2015) - Leitinger, Georg; Ruggenthaler, Romed; Hammerle, Albin; Lavorel, Sandra; Schirpke, Uta; Clement, Jean‐Christophe; Lamarque, Pénélope; Obojes, Nikolaus; Tappeiner, Ulrike
Abstract: This study analyzes the impact of droughts, compared with average climatic conditions, on the supporting ecosystem service water provision in sub‐watersheds in managed alpine grasslands in two climatically different regions of the Alps, Lautaret (French Alps) and Stubai (Austrian Alps). Soil moisture was modelled in the range of 0–0.3 m. At both sites, current patterns showed that the mean seasonal soil moisture was (1) near field capacity for grasslands with low management intensity and (2) below field capacity for grasslands with higher land‐use intensity. Soil moisture was significantly reduced by drought at both sites, with lower reductions at the drier Lautaret site. At the sub‐watershed scale, soil moisture spatial heterogeneity was reduced by drought. Under drought conditions, the evapotranspiration to precipitation ratios at Stubai was slightly higher than those at Lautaret, indicating a dominant 'water spending' strategy of plant communities. Regarding catchment water balance, deep seepage was reduced by drought at Stubai more strongly than at Lautaret. Hence, the observed 'water spending' strategy at Stubai might have negative consequences for downstream water users. Assessing the water provision service for alpine grasslands provided evidence that, under drought conditions, evapotranspiration was influenced not only by abiotic factors but also by the water‐use strategy of established vegetation. These results highlight the importance of 'water‐use' strategies in existing plant communities as predictors of the impacts of drought on water provision services and related ecosystem services at both the field and catchment scale. © 2015 The Authors. Ecohydrology published by John Wiley & Sons, Ltd.